COMPATIBILITY OF ISLAM AND CAPITALISM: DIMENSIONS OF CAPITALISM IN THE QURAN - Baharuddin, Didin; Anwar, Hamdani (Peminat Ilmu Ushuluddin, 2023)
This study aims to explore the compatibility of capitalism and Islam. Capitalism, which is identical with self-centeredness and greed, is often at odds with Islam. Have we employed some descriptive, interpretation, and philosophical approaches, this study concludes that capitalism and Islam are compatible. The Quran mentions several characteristics of capitalism, such as private ownership and profit maximization. Private ownership and capital accumulation are permitted in Islam, and the freedom to own property is a measure of productivity. Profit maximization, which is the core of capitalism, is also available in the Quran. Islam permits profit-taking within certain parameters. This situation demonstrates the compatibility of capitalism and Islam. However, it is necessary to incorporate Islamic norms to make capitalism more compatible with Islam.